From nature to the laboratory, an effort to raise disaster awareness - Afrian, Ramdan (American Institute of Physics Inc., 2023)
Aceh is one of the provinces in Indonesia with a high risk of disaster. The threat of disasters in the form of forest and land fires, tornadoes, floods, flash floods, ROB floods, landslides, extremes and abrasions often occur in Aceh, namely 365 disaster events from January to June in 2021. Based on the calculation of the disaster ratio index it is known that in 2020 Aceh obtained a value of 153.58 which belongs to the high class. Almost all areas of Aceh have a red color that indicates that the value of the disaster ratio index in Aceh is more than 144. The above conditions require the people of Aceh to be able to have awareness of the disaster that will befall him and his family. Therefore, there needs to be efforts to increase awareness of disasters in the community, one of which is through education. Aceh which has a form of local wisdom about the disaster can increase public disaster awareness if it can be understood or studied by the community. Therefore, local wisdom derived from nature needs to be legalized or made management in the form of natural laboratories. This is so that learners, the general public or academics can learn and adapt the local wisdom to their living environment or can convey toothers. Thus, it is expected that public disaster awareness will increase. This is in accordance with the results of Crismono's research where natural learning and integration of local knowledge can increase the development of community capacity in disaster management as well as Wulansari which found results where research from the use of natural laboratories can increase the biological learning outcomes of learners by 80 © 2023 Author(s).